colocando na forma ax² + bx + c = 0 a equação x (x-2) + 1 =2 (x+3) sera:
a)x² + 2x + 2 = 0
b)4x² + 12x + 9 = 0
c)2x² - 7x + 1 = 0
d)x²- 4x - 5 = 0
Soluções para a tarefa
Respondido por
0
Resposta:
letra d) x² - 4x - 5=0
Explicação passo-a-passo:
⇒irá fazer uma distributiva:
x(x-2)+1=2(x+3)
x²-2x+1=2x+6
x²-2x-2x+1-6=0
x²-4x-5=0
Perguntas interessantes
Administração,
9 meses atrás
Português,
9 meses atrás
Administração,
9 meses atrás
História,
11 meses atrás
Contabilidade,
11 meses atrás
Física,
1 ano atrás
Artes,
1 ano atrás